Development and application of metal contacts on polycrystalline diamond films using combination of HF and arc plasma sources - Muratov, R.M.; Vierovkin, A.A.; Kutny, V.E.; Nezovibat’ko, Yr.N.; Rybka, A.V.; Taran, V.S. (Вопросы атомной науки и техники, 2014)
In this paper, the technology of application of ohmic contacts using arc discharge assisted by HF field was developed for semiconductor radiation detectors production. Polycrystalline diamond material for production of detectors was synthesized by chemical vapor deposition method (CVD) in NSC KIPT. Bilayer contacts were deposited on polycrystalline CVD (pCVD) diamond films, where the first layer was chromium, and the second layer – copper or stainless steel respectively. Electro-physical characteristics of pCVD diamond detectors with different contact materials were studied.